2013
DOI: 10.1007/s13105-013-0256-5
|View full text |Cite
|
Sign up to set email alerts
|

Ergogenic effect of dietary L-carnitine and fat supplementation against exercise induced physical fatigue in Wistar rats

Abstract: L-carnitine (LC) plays a central role in fatty acid metabolism and in skeletal muscle bioenergetics. LC supplementation is known to improve physical performance and has become widespread in recent years without any unequivocal support to this practice. A scientific-based knowledge is needed, to understand the implications of LC supplementation on physical fatigue. In current study, we have explored synergistic effects of dietary LC and fat content against physical fatigue in rats. Ninety male Wistar rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In addition, the antioxidant enzyme system protects against excessive or exhaustive exercise-induced oxidative damage, and is associated with physical status in athletes (14). Enhanced antioxidant enzyme activity prolongs exercise performance, and (15,16). The identification of natural antioxidants originating from plants has been an area of increased attention (17).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the antioxidant enzyme system protects against excessive or exhaustive exercise-induced oxidative damage, and is associated with physical status in athletes (14). Enhanced antioxidant enzyme activity prolongs exercise performance, and (15,16). The identification of natural antioxidants originating from plants has been an area of increased attention (17).…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs are usually administrated to alleviate muscle soreness after exercise (Schoenfeld 2012). In addition, L-carnitine was reported to decrease the muscle fatigue induced by acute exercise (Pandareesh & Anand 2013), and the administration of non-essential amino acid citrulline showed an increased swimming time until exhaustion and reduced muscle fatigue (Takeda et al 2011). Resveratrol, the active compound of red grapes, has been shown to improve exercise performance and oxygen consumption, and these effects were mediated by the activation of mitochondrial biogenesis (Dolinsky et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Pandareesh and Anand [11] reported that LC supplementation with a 10 or 15% fat diet enhanced endurance with increased tissue levels of ATP and glycogen in rats, but not with a 5% fat diet. Similarly, our study also showed that LC with HFD (45% fat from calories) feeding improved energy metabolism and endurance, although we did not observe those changes with a lowfat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is some evidence showing that LC supplementation improves endurance capacity with increased oxygen uptake or fatty acid oxidation [10e12], however others did not observe the positive influences of LC supplementation on endurance capacity and energy metabolism during exercise [13e15]. Most recently, Pandareesh and Anand [11] reported that the supplementation of LC with fat increased the exhaustive swimming time and reduced glycogen consumption in the liver and muscle in rats, but they did not observe changes in skeletal muscle oxidative metabolism. Thus, we here investigated the effects of LC on endurance capacity and related physiological metabolism using the treadmill system, which has the distinct advantage over other forms of exercise, including swimming, in that the total amount of external work done by the experimental animal can be calculated easily [16].…”
Section: Introductionmentioning
confidence: 99%